The Value Of Religiousness In The Udhik-Udhikan Tradition In The Village Of Pandangan Wetan Kragan District Rembang Regency: (Study of Coastal Folklore on the North Coast of Java Island) - Santi Paramita (Jurnal Pendidikan, Sains Sosial, dan Agama, 2024)
This research aims to describe the Udhik-udhikan tradition in the Pandangan Wetan village, Kragan District, Rembang Regency, regarding: how it is implemented, what its religiosity values ​​are, what its philosophical meaning is, and how the Udhik-udhikan tradition functions for its supporting community. This research is qualitative research. -descriptive, data sources come from informants, photographs and reference sources. Data collection techniques are through interviews, observation, documentation and literature review. Data validity techniques use source triangulation, while data analysis techniques use the stages of data description, data analysis and interpretation. The results of the research show that (1) Udhik-udhikan is carried out by residents when they want to express their gratitude. (2) The value of religiosity in tradition has another side, namely that people are more optimistic and have a big spirit. (3) The philosophical meaning behind the tradition is to give alms to all beings. (4) Udhik-udhikan has three functions; a. Religious function; b. Social and community functions; c. Cultural function; ( 1) As a means of a projection system (projective system), (2) As an educational tool, and (3) As a supervisor of societal norms that must be obeyed by the collective.